Attitudes of Landspitali’s Managers toward Lean Management - Guðjónsdóttir, Kristjana; Möller, Eðvald; Rosenkjær, Eydís Ý.; Hallgrímsdóttir, Vigdís (Croatian Interdisciplinary Society, 2024)
This research aimed to evaluate the implementation of lean management at Landspitali, the National University Hospital of Iceland, by examining the current state of the methodology, the effectiveness of the methodology, and the factors influencing managerial attitudes and outcomes in the hospital. The study provides actionable insights to optimise lean management practices in healthcare and offers guidance for future improvements. Using a mixed-methods approach, the research combined quantitative and qualitative analyses. The quantitative component involved a questionnaire with 18 questions distributed to 115 managers at Landspitali. The findings revealed that while most managers were familiar with the lean management methodology, many needed more confidence in its effectiveness, mainly due to insufficient information about its benefits. These results underscore the need for enhanced communication and education to build confidence and motivation among managers, thereby supporting more effective implementation at Landspitali and similar institutions. Additionally, the study identified a critical need for further training and development among staff – for example, through the establishment of a dedicated training academy focused on lean management methods. This initiative will address the gaps highlighted in the research, ensuring more effective implementation and sustained success.